Upaya Prodi BK STKIP Budidaya dalam Menanggulangi Gelandangan dan Pengemis di Wilayah Kota Binjai - Fatmawati Sitepu; Nurul Hasanah; Muhammad Riza Darwin (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
The issue of homeless individuals and beggars (gepeng) is a complex social phenomenon reflecting structural poverty and social inequality. This study focused on individuals categorized as People with Social Welfare Problems (PPKS) at the Binjai City Technical Implementation Unit (UPTD) for Social Services for the Homeless and Beggars. The research employed the Participatory Action Research (PAR) method. Data were collected through observation, in-depth interviews with key informants—specifically the PPKS and social workers at the facility—and a review of relevant documents. The study aimed to examine the implementation of efforts to address the issue of homelessness and begging by the Guidance and Counseling (BK) Study Program at STKIP Budidaya, as well as the impact of these activities. The findings indicate that the community empowerment activities—designed to boost life motivation and foster a better quality of life—were effective. This effectiveness was evidenced by the participation and enthusiasm shown by the PPKS throughout the activities